EXPERIENCE OF COSMETIC REHABILITATION IN PATIENTS WITH POST-TRAUMATIC EYEBALL’S SUBATROPHY - L. M. Curova; Ye. S. Milyudin; K. Yu. Kondrashova (Oftalʹmologiâ)
Purpose: to estimate the indications for prosthesis in patients with eye’s subatrophy without pre-enucleation or evisceration and after it.Patients and methods: There were 152 patients with post-traumatic subatrophy (av.age — 46,1 years) under supervision since 2010 till 2017. Group I — 102 patients (67,1%) with locomotory stump after enucleation: 56 (55%) — after enucliation, 46 (45%) — after eviciration. Group II — 50 patients (32.9%) with prosthesis without prior enucliation or eviciration. All patients underwent visometry, biomicroscopy, ultrasonic biometry, ultrasound B scan, tonometry, radiography and computed tomography of cranium, as well as an im-munological examination of the blood to detect the presence of sensitization to the tissues of the eye. The indications for enucliation in group I were I stage of subatrophy combined with post-traumatic subacute uveitis and sympathetic ophthalmia threatened the second eye [38 (37,2%) eyes] and II and III stage of eyeball’s subatrophy with fast and slow progressive form [64 (85,3%) eyes]. There were 58 (56.8%) men, 41 (40.2 %) women и 3 (3.0%) children in I group. Prosthesis was made for 22 patients (44%) with 2 stage of subatrophy and 28 (56%) with 3 stage. There were 44 (84.3%) adults [28 (66.7%) men, 16 (33.3%) women] и 6 (15,7%) children. The remaining sensitization to the vascular antigen with the background of steroid therapy is an absolute indication for eyeball’s removal in posttraumatic subatrophy. Contraindications to prosthetics of subatrophic eyes without preliminary enucleation or evisceration are positive results of immunological examination of blood, clinical manifestations of slow uveitis, high intraocular pressure and recurrent giphemes. According to our observations, it was possible to perform cosmetic rehabilitation without removing the eyeball in the late post-traumatic period (10–12 months after injury) in the absence of sensitization to the S-antigen of the eye tissues in 32.9% patients with posttraumatic subatrophy.Conclusion. Enucleation was and remains a radical treatment method of posttraumatic subatrophy. For the best cosmetic results of prosthetics, eye removal should be performed with the formation of the locomotor stump and implantation of the orbital inserts.